2023
DOI: 10.1128/mbio.00052-23
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Associated Augmentation of Gut Microbiome Virulence Capability Drives Sepsis Severity

Abstract: Older adults suffer more frequent and worse outcomes from sepsis, a critical illness secondary to infection. The reasons underlying this unique susceptibility are incompletely understood.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In recent years, the focus has shifted toward understanding the specific mechanisms by which these microorganisms can induce pathogenic effects [ 10 , 11 ]. One such mechanism relies on the presence of virulence factors (VFs) encoded by the microbial genome [ 12 ]. VFs are molecular components or proteins produced by microorganisms that enhance their ability to colonize and infect host tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the focus has shifted toward understanding the specific mechanisms by which these microorganisms can induce pathogenic effects [ 10 , 11 ]. One such mechanism relies on the presence of virulence factors (VFs) encoded by the microbial genome [ 12 ]. VFs are molecular components or proteins produced by microorganisms that enhance their ability to colonize and infect host tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the present study has focused on the impact of aging on the host with an emphasis on innate immunity. Two recent studies ( 33 , 34 ) have reported that aging alters the stability and/or potency of gut bacteria, and such an effect of aging might modulate the severity of sepsis caused by bacteria of gut origin. Further studies are warranted to identify the factors from gut bacteria of old subjects that exacerbate sepsis severity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been growing interest in elucidating the precise mechanisms through which microorganisms exert pathogenic effects ( Liu et al, 2022 ; Rudin et al, 2023 ). One such mechanism involves the presence of virulence factors genes (VFGs), which are encoded by the microbial genome ( Colbert et al, 2023 ). VFGs are molecular components or proteins produced by microorganisms to enhance their capacity to colonize and infect host tissues ( Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%